A Place in the World : New Local Historiographies in Africa and South Asia - Harneit-Sievers, Axel, (Brill Book Archive Part 1, ISBN: 9789004472495., 2002)
Local histories, written and published by non-academic historians, constitute a rapidly expanding genre in contemporary non-Western societies. However, academic historians and anthropologists usually take little notice of them. This volume takes a comparative look at local historical writing. Thirteen case studies, set in seven different countries of sub-Saharan Africa, India and Nepal, examine the authors, their books and their audiences. From different perspectives, they analyse the genre's intellectual roots, its relationship to oral historical narratives, and its relevance and impact in local and wider arenas. Local histories, it turns out, pursue a variety of agendas. They (re)construct local and communal identities affected by rapid social change. Often, they (re)write history as part of cultural and political struggles. Openly or implicitly, all of them place local communities on the map of the world at large.